TINGKAT KEPUASAN PESERTA PAMERAN PADA PAMERAN KERAJINAN NASIONAL - Rudhi Achmadi (LPPM Universitas Asa Indonesia, 2016)
The quality of service provided by PT. Mediatama Binakreasi to its customers (exhibitors of Crafina 2014) is one of the important aspects for the company's marketing. This will affect the sustainable competitiveness of the business as one of the famous Professional Exhibition Organizers (PEO) in Indonesia to compete with others. This study discusses three important issues: a) expectations of the exhibitors on the performance of PT. Mediatama in organizing national level craft fairs (Crafina Expo 2014), b). The level of satisfaction of the exhibitors on the performance of PT. Mediatama Binakreasi, and c) what steps need to be done to meet the expectations of exhibitors in the exhibition. The purpose of this study is to determine a). expectations of the exhibitors on the performance of PT. Mediatama in organizing national level craft fairs (Crafina Expo 2014), b). the level of satisfaction of the exhibitors on the performance of PT. Mediatama Binakreasi, and c) what steps need to be done to meet the expectations of the exhibitors. The method of analysis used in this research is the analysis of quadrant (quadrant analysis), whereas the data obtained from questionnaires to a sample, interview and observation. Based on the research results, it can be concluded that there is gap between the expectations of the exhibitors and the performance of PT. Mediatama Binakreasi at craft fairs nationwide (Crafina 2014) held at the Jakarta Convention Center on 26 to 30 November 2014. It can be seen from the level of interest / expectations by 94.24% while the value of contentment only amounted to 85.27%, the difference is 8.97%. In addition, management has not yet implemented some attributes that are considered to be factors that affect customers’ satisfaction, including the elements that are considered important, such as: the arrangement of the exhibition facility design, accuracy in recording transactions, and process services to exhibitors in 2014 Crafina. Based on the conclusion, the author then gives advice namely: management on future occasions should further improve the quality of service in all aspects to the exhibitors due to the persistence of the gaps between expectations and satisfaction levels. The need to continue to get feedback from customers (exhibitors) or desire to know the expectations of the exhibitors and also the need to build a shared commitment throughout the human resources available for the provision of excellent service to the exhibitors. Thus, knowing the deficiency in the management and other services, this step also serves to maintain the satisfaction of exhibitors and also to enhance the corporate image.